E-shock 2000 : the electronic shopping revolution : strategies for retailers and manufacturers - De Kare-Silver, Michael (Basingstoke : Macmillan, 2000)
This book is about: Definitions and customer trends; Learning from the pioneers in electronic selling; Future growth of electronic shopping; Ten strategic options for retailers; The store of the future; ...
Keywords: Trade; Electronic commerce; Interactive marketing; Retail trade -- Technological innovations; Retail trade; Electronic commerce